Relationship between middle school students' academic stress and physical exercise behavior from the perspective of Self-Determination Theory: The chained mediation of motivation and intention. - Kegang Zhao; Yichen Zhao; Weiqiang Xu (PLoS ONE)
Academic stress is associated with lower engagement in healthy behaviors, including physical exercise, among middle school students. Based on Self-Determination Theory, this study examines the association between academic stress and physical exercise behavior among middle school students, exploring the mechanisms through the chained mediation of motivation and intention. Scales used in this study include the Academic Stress Scale, Autonomous and Controlled Motivation Scales, and Physical Exercise Intention and Behavior Scales to measure relevant variables. This cross-sectional study involve 290 middle school students (116 males, age = 13.76±0.96 years, grades 7-9) selected from a middle school in Xiamen, China. Structural equation modeling is used to analyze the data, revealing the following results: (1) Academic stress is significantly associated with middle school students' exercise behavior through the mediating role of exercise intention; (2) Controlled motivation, autonomous motivation, and exercise intention serve as chained mediators between academic stress and exercise behavior; (3) Academic stress is not associated with exercise intention through the parallel mediation of controlled and autonomous motivations. These findings provide new insights into the relationship between academic stress and physical exercise behavior in middle school students.